Endoscopic ultrasound-guided choledochoduodenostomy with a lumen-apposing metal stent through an uncovered metal duodenal stent - Sportes, Adrien; Airinei, Gheoghe; Kamel, Ralph; Raynaud, Jean Jacques; Benamouzig, Robert (Endoscopy International Open, 2018)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) in patients with a preexisting duodenal stent is particularly challenging and has a low success rate. Endoscopic ultrasound (EUS)-guided biliary drainage (EUS-BD) has been increasingly used as an alternative to percutaneous transhepatic biliary drainage after failed ERCP. EUS-guided choledochoduodenostomy (EUS-CD) and EUS-guided hepaticogastrostomy (EUS-HGS) have been reported to have similar efficacity. Recently, a novel dedicated fully-covered lumen-apposing metal stent (LAMS) has been developed for EUS-CD (Hot AXIOS; Boston Scientific, Massachusetts, United States). It seems that this new device decreases the morbidity of EUS-CD. We present a case in which EUS-CD with LAMS through an uncovered metal duodenal stent was used successfully.